Primary plasma cell leukaemia - Dimopoulos, M.A.; Palumbo, A.; Delasalle, K.B.; Alexanian, R. (British Journal of Haematology, 1994)
Among 750 previously untreated patients with multiple myeloma, 27 (4%) presented with plasma cell leukaemia. All but one patient had high tumour mass and, when compared with comparable patients without leukaemia, more frequent extraosseous involvement, thrombocytopenia, high serum lactate dehydrogenase and hypodiploid plasma cells. Most patients also had complex cytogenetic abnormalities. Treatment with standard melphalan-prednisone was ineffective, with a median survival of 2 months, but more intensive chemotherapy induced responses in approxirnately one-half of the patients, with a median survival of 20 months. Primary plasma cell leukaemia usually results from the proliferation and extramedullary expansion of immature plasma cells and requires prompt and intensive chemotherapy.
Keywords: Chemotherapy; myeloma; Plasma cell leukaemia